The promotion system at high school: criteria of the educational community - Chaves Salas, Ana Lupita (2017)
The purpose of this article is to reveal the research project results that took place in the Educational Research Institute (INIE), Education School, at the University of Costa Rica (UCR). The research main objective was to analyze the educational community`s criterion related to “Reform of regulatory rules of promotion and repetition in the Costa Rican educational system”. Furthermore, this research involved a change in the promotion system of the secondary students in curriculum, teaching, and administrative aspects. Moreover, the objective was achieved by using a descriptive exploratory qualitative research methodology, in which the educational community of two public secondary schools, Ministry of Education authorities (MEP), university professors, and the National Association of Teachers (ANDE) participates. This research begins with the reform´s antecedents and then a literature review about the topic. Therefore, there is evidence in this study related to the educational community`s disagreement about this reform and they propose suggestions in order to improve the high school Promotion System in Costa Rica.